A meta‐analysis of fish behavioural reaction to underwater human presence. Issue 5 (24th May 2019) - Samia, Diogo S. M.; Bessa, Eduardo; Blumstein, Daniel T.; Nunes, José A. C. C.; Azzurro, Ernesto; Morroni, Lorenzo; Sbragaglia, Valerio; Januchowski‐Hartley, Fraser A.; Geffroy, Benjamin
Abstract: In an increasingly anthropic world, humans have profound impacts on the distribution and behaviour of marine fishes. The increased human presence has modified fishes' antipredator behavioural responses, and consequently flight decisions, as a function of their changed perceptions of risk. Understanding how fish react to human presence can help identify the most vulnerable functional groups/species and estimate impacts caused by human disturbance. Shoal and body size are known to influence fish flight initiation distance (FID; the distance between the predator and prey when the prey begins to escape); however, few studies attempt to test the moderators of these relationships. Here, we present a comprehensive meta‐analysis evaluating FID of fish in response to human presence. Specifically, we investigated six candidate moderators that could influence the relationship between FID with shoal and body size. Our results showed that individual fish size was strongly and positively correlated with FID and the most important moderator that explained the variance in individual body size‐FID relationship was shoaling behaviour. However, and somehow surprisingly, we detected no significant relationship between shoal size and FID. We discuss how these results can inform the development of fish conservation strategies and ultimately assist in the management of marine protected areas.